(untitled) (World Bulletin of Social Sciences, 2021)
To study the prevalence of dental disease and chronic catarrhal gingivitis in children with disabilities; determination of some biochemical parameters of oral fluid in the diagnosis, treatment and prevention of chronic catarrhal gingivitis in children with disabilities; evaluation of physical and chemical parameters of oral fluid in chronic catarrhal gingivitis in children with disabilities; analysis and development of a profile algorithm for early diagnosis, treatment and prevention of chronic catarrhal gingivitis in children with disabilities